2020
DOI: 10.21203/rs.3.rs-116972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into Phylogenetic Relationships and Genome Evolution of Subfamily Commelinoideae (Commelinaceae Mirb.) Inferred from Complete Chloroplast Genomes

Abstract: BackgroundCommelinaceae (Commelinales) comprise 41 genera and widely distributed in both the Old and New Worlds except Europe. The relationships among genera in this family have been suggested in several morphological and molecular studies. However, it is difficult to explain their relationships due to high morphological variations and low support values. Nowadays, many researchers are commonly using complete chloroplast genome data for inferring evolution of land plants. In this study, we completed 15 new chl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…In the Eriocaulon chloroplast genomes, we found 33 to 58 SSR loci. Other studies have shown that the most abundant SSRs were A/T-rich mononucleotide repeats, which was consistent with the chloroplast genome's common polyA or polyT repeats and rare G or C repeats [35,[51][52][53]. Dinucleotide repeats were the most common type in the Eriocaulon chloroplast genomes (Table 2) and had high AT content.…”
Section: Chloroplast Genome Evolution Of Eriocaulonsupporting
confidence: 75%
“…In the Eriocaulon chloroplast genomes, we found 33 to 58 SSR loci. Other studies have shown that the most abundant SSRs were A/T-rich mononucleotide repeats, which was consistent with the chloroplast genome's common polyA or polyT repeats and rare G or C repeats [35,[51][52][53]. Dinucleotide repeats were the most common type in the Eriocaulon chloroplast genomes (Table 2) and had high AT content.…”
Section: Chloroplast Genome Evolution Of Eriocaulonsupporting
confidence: 75%
“…In most plants, the IRb and SSC boundary lie on the ycf1 gene, which may be associated with the expansion of the IRb/SSC boundary (Kumar et al, 2018). In the cp genome of A. ukurunduense, we also observed the ycf15 gene, which exists in most angiosperms but whose function remains unknown (Shi et al, 2013;Jung et al, 2021). Compared with the LSC and SSC regions, GC content in the IR region was the highest, mainly due to four rRNA genes occupying a greater area.…”
Section: Cp Genome Structurementioning
confidence: 75%